Preparation of a zeolite supported Ti02 photocatalyst via metal organic chemical vapor deposition (MOCVD) To Photodegrade Organic Pollutants - Collin G. Joseph; Awang Bono; Sharain Liew Yen Ling; Rubia Idris (Universiti Malaysia Sabah, 2014)
Photo degradation of Indigo Dye (I D) in aqueous solution using anatase Ti02 and TiO2/zeolite photo catalyst were studied and presented in this technical report. The photo catalysts were prepared using sol-gel method and subsequently calcined in a furnace at 450°C for 4 hours. The photo catalysts were characterized using SEM and XRD analysis techniques. The XRD analysis was used to identify and confirmed the formation of anatase Ti02 crystalline structure while the SEM analysis was used to study the surface morphology of the TiO2/zeolite surface. About 0.4 g of the photocatalysts was used in varied concentration (10-20 mg/L) to photodegrade 500 mL of unbuffered Indigo Dye solution in this photodegradation system. A comparison study was also done using neat anatase Ti02 and TiOJzeolite photocatalyst systems to evaluate the synergistic effect of using a combined adsorbent-photo catalyst system to treat dye contaminated wastewater. UV-Vis spectroscopy was used to determine the concentration of the extracted sample with Indigo Dye's Amax of 725 nm. The photo degradation experiments were conducted over a 5 hour duration to determine the synergistic effect of the newly synthesized adsorbent-photo catalyst degradation in each experiment. The results showed that photo catalytic behavior of TiO2/zeolite was better as the degree of degradation for TiO2/zeolite was higher as compared with neat Ti02. The percentage degradation achieved by using TiO2/zeolite in 10 mg/L and 20 mg/L were 60.65% and 75.83% respectively. The degradation process followed a pseudo-first-order kinetic reaction with the regression correlation, R2, in the range of between 0.8584 and 0.9624. Whereas the rate constant, k, for the photo degradation of Indigo Dye solution was in the range of between 0.1207 h-1 and 0.2669 h-1, The highest values obtained for the TiO2/zeolite were 0.2669 h-1 and 0.1736 h-1 respectively, demonstrating the suitability of using this combined adsorbent-photo catalyst treatment system in dye contaiminated wastewater.